-6m-9=-2+3(6m+7)

Simple and best practice solution for -6m-9=-2+3(6m+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6m-9=-2+3(6m+7) equation:



-6m-9=-2+3(6m+7)
We move all terms to the left:
-6m-9-(-2+3(6m+7))=0
We calculate terms in parentheses: -(-2+3(6m+7)), so:
-2+3(6m+7)
determiningTheFunctionDomain 3(6m+7)-2
We multiply parentheses
18m+21-2
We add all the numbers together, and all the variables
18m+19
Back to the equation:
-(18m+19)
We get rid of parentheses
-6m-18m-19-9=0
We add all the numbers together, and all the variables
-24m-28=0
We move all terms containing m to the left, all other terms to the right
-24m=28
m=28/-24
m=-1+1/6

See similar equations:

| 3x/2x=x/10-6/5 | | 2j^2-7j+5=0 | | 4s^2-s-3=0 | | 3x2−x=x10−65 | | (x-7)^2-108=0 | | 12x^2+16×+5=0 | | 3x+175=9.25 | | 2(x+3)+3(x-1)=138 | | 7k-4=5+9k | | x=4.6*((x+9.8)/9.5) | | 2x/8=10 | | 9x-30=-75 | | 2/3×+y=4/3 | | 3d^2-6=0 | | 2(-4x-8)=-24 | | -(x+4)-6(x-5)=40 | | X=123x= | | X-(-6)+9+2x-19=23 | | -4|8-5m|=13 | | 5x+3x=7x+6 | | 2(7-7x)=14 | | -41/6=2/3n+11/4n | | -7a+10=-8(a+11) | | 9y4+65y2−144=0 | | 5z-2z=-3 | | (4x/5)+7=6 | | -6+x/6=2 | | 2x+10=3x+65 | | 4(x-7)+6x=32 | | 5(6b-6)-3(b-2)=-51 | | −6x−1+5x^2=8x^2 | | 3x+6-2=-2 |

Equations solver categories